Kharkiv region of Ukraine in the aspect of a polycentric development model - Nyemets, K.; Sehida, E.; Guseva, N.; Klychko, L. (Paris: “Paris University Press”, 2016)
This article is devoted to the analysis of a model of regional development of Kharkiv region of Ukraine, which is monocentric, and the rationale for the formation of polycentrism in the region. The city of Kharkiv and urban areas as centers of growth in the region are considered in the article
Keywords: regional development; polycentric development; monocentric development; cities as centers (poles) of the growth; in the region; urbanized area